Field notes and Hank Zaletel letter to Thomas H. Kent. spring 1997 - Zaletel, Hanket al (1997)
List of birds and locations contributed by Hank Zaletel. Included with the field report is a note from Hank Zaletel to Thomas H. Kent regarding additional bird sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1997. Epson - sheet feed